Interactional Style Features Used by Mark Baum In the Film The Big Short - William Wijaya; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study focuses on analyzing the features of interactional style used by Mark Baum when talking to his interlocutor with different statuses on business related topics. In conducting this study, the writer used the theory of Interactional styles by Holmes (2006). This study was done using a qualitative approach. The result of this study showed that Mark Baum used both feminine and masculine features of interactional style when talking to his interlocutors with different statuses. The writer also found out that the use of features of interactional style, such as aggressive interruption, direct, and autonomous, can be affected by the difference of status. Moreover, Mark Baum also uses masculine features of interactional style more than feminine features of interactional style when talking to his subordinates.